Ixodes ventalloi: a vector role to be explored - Santos, A.S. (2018)
Ixodes ventalloi is still a poorly studied tick and its public health relevance largely unknown. In Portugal it is known to share habitats with Ixodes ricinus in mainland littoral areas and to parasitize a variety of wild and domesticated animals and also humans. The potential involvement of I. ventalloi in the natural cycle of tick‐borne agents was first suggested by the detection of a new variant of Anaplasma phagocytophilum in questing and cat‐feeding ticks from Setúbal and Santarém, and is again questioned here. In this study we present the detection of A. phagocytophilum, Candidatus Neoehrlichia mikurensis and Coxiella burnetii in questing I. ventalloi collected from Parque Florestal de Monsanto (PFM), a Lisbon recreational park.